Creation of Islamic state between ambition and ignorance: study on Tadfir Wa al-Hijrah in Indonesia and their interpretation toward the Qur’anv - Solihin, Sohirin Mohammad (s.n, 2012)
The research attempts to study on the emergence of certain group of Muslim hard-liners in Indonesia who have the ambition to create Islamic state. They group felt disappointed when Muslim leaders were defeated in their constitutional den=bate to lay down principle of an Islamic government by national leaders